(untitled) (Research, Society and Development, 2022)
Biopolitics is a term developed by Foucault to designate a set of management control practices and the life of populations, developed by states, mostly neoliberals, as a way to establish governmentality, which in turn needs to institute social inequalities for the organization of political rationality. In this scenery, the school is a space for the consolidation of the interests of the elite as a way to perpetuate its status quo. In the case of Brazil, there are numerous manifestations of biopolitical practices in education, such as the proliferation of educational policies following the market ordination. This text aims to discuss financial education based on foucaultian concepts of governmentality and biopolitics as a disciplinary society that structures class and society control, always aiming at maintaining order and morality. This is a section of the master’s thesis "Financial Education and Minor Education: curricular experiments with a 9th year class in Ji-Paraná/RO", developed with the Graduate Program in School Education - Master and Professional Doctorate (PPGEEProf), of the Federal University of Rondônia.